3-D Bioprinting in cartilage tissue engineering for bioinks-short review. (2023) - Raut, A.V.; Agrawal, A.; Bagde, A.; Fulzele, P.; Quazi Syed, Zahiruddin
Abstract: This short review focuses on developments in the field of bioprinting for cartilage tissue engineering, along with discussion on the various approaches for cartilage fabrication. The methods (cell-laden, cell-free and a combination of both) involved intended to obtain microenvironment to cells for better development and cell growth using the said methods. The controlled dimension of the scaffold can be decided with great precision. The hybrid bioprinting of cell laden and cell-free materials gives the most promising results for cartilage tissue engineering with multiple materials bio-print including high strength polymers. Although hybrid technology is new but currently 3D-printing for cartilage applications is in high demand, and complete conversation on the current and future viewpoints is presented in this review.